Dual Independent Roles of the p24 Complex in Selectivity of Secretory Cargo Export from the Endoplasmic Reticulum - Lopez, Sergio; Perez-Linero, Ana Maria; Manzano-Lopez, Javier; Sabido-Bozo, Susana; Cortes-Gomez, Alejandro; Rodriguez-Gallardo, Sofia; Aguilera-Romero, Auxiliadora; Goder, Veit; Muñiz, Manuel (Cells (Basel, Switzerland), 2020)
The cellular mechanisms that ensure the selectivity and fidelity of secretory cargo protein transport from the endoplasmic reticulum (ER) to the Golgi are still not well understood. The p24 protein complex acts as a specific cargo receptor for GPI-anchored proteins by facilitating their ER exit through a specialized export pathway in yeast. In parallel, the p24 complex can also exit the ER using the general pathway that exports the rest of secretory proteins with their respective cargo receptors. Here, we show biochemically that the p24 complex associates at the ER with other cargo receptors in a COPII-dependent manner, forming high-molecular weight multireceptor complexes. Furthermore, live cell imaging analysis reveals that the p24 complex is required to retain in the ER secretory cargos when their specific receptors are absent. This requirement does not involve neither the unfolded protein response nor the retrograde transport from the Golgi. Our results suggest that, in addition to its role as a cargo receptor in the specialized GPI-anchored protein pathway, the p24 complex also plays an independent role in secretory cargo selectivity during its exit through the general ER export pathway, preventing the non-selective bulk flow of native secretory cargos. This mechanism would ensure receptor-regulated cargo transport, providing an additional layer of regulation of secretory cargo selectivity during ER export.